Epidemiology of Rotavirus and Cholera in Children Aged Less Than Five Years in Rural Bangladesh (Journal of Health, Population and Nutrition, 2011)
Despite the known presence of rotavirus-associated diarrhoea in Bangladesh, its prevalence, including records of hospitalization in rural health facilities, is largely unknown. In a systematic surveillance undertaken in two government-run rural health facilities, 457 children, aged less than five years, having acute watery diarrhoea, were studied between August 2005 and July 2007 to determine the prevalence of rotavirus. Due to limited financial support, the surveillance of rotavirus was included as an addendum to an ongoing study for cholera in the same area. Rotavirus infection was detected in 114 (25%) and Vibrio cholerae in 63 (14%) children. Neither rotavirus nor V. cholerae was detected in 280 (61%) samples; these were termed ‘non-rotavirus and non-cholera’ diarrhoea. Both rotavirus and cholera were detected in all groups of patients (